Physical Activity Component Should be Included when Designing National Child-Obesity Program: The Rapid Review of Multi-Component Child Obesity Intervention Programs - Don Hyung Lee (Asian Society of Kinesiology, 2020)
OBJECTIVES The prevalence of child obesity is steadily increasing in Korea, thus government needs to seek for effective intervention programs to counteract current epidemics. This study sought to find proven effective child obesity programs implemented in other countries in order to provide policy recommendation. We report the results of rapid review of child obesity programs which were implemented outside of Korea. METHODS A search of multiple databases (NICE Evidence Search, Open Grey, Grey Literature Report, National Cancer institute: research-tested intervention programs) was conducted to identify relevant research articles published after January 2010. RESULTS 11 studies met the inclusion criteria after systematic screening. Most of the included studies used physical activity & diet/nutrition at the same time, while school was the most common location for the intervention. 5 studies showed improvement in obesity related outcomes. Interventions contained physical activity & diet/nutrition or physical activity & psychological coaching, and intervention implemented in school, healthcare facility, summer camp, and after-school class were shown effective. CONCLUSIONS Considering the results of current review, multi-component intervention which includes physical activity is recommended when designing child obesity program. The location of the intervention should be school to maximize its effectiveness.